2014
DOI: 10.1007/s00436-014-4197-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil is the origin for the presence of Naegleria fowleri in the thermal recreational waters

Abstract: Naegleria fowleri is found in most geothermal baths of Guadeloupe and has been responsible for the death of a 9-year-old boy who swam in one of these baths in 2008. We wanted to determine the origin for the presence of this amoeba in the water. Water samples were taken at the origin of the geothermal sources and at the arrival in the baths. After filtration, cultures were made and the number of Naegleria present was determined using the most probable number method. Soil samples collected in the proximity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Amoebic encephalitis can also be caused by Balamuthia mandrillaris and Naegleria fowleri (Excavata, Heterolobosea) (Visvesvara et al, 1993;Schuster and Visvesvara, 2004;Visvesvara et al, 2007;Siddiqui and Ahmed Khan, 2012). The finding of related SSU rRNA sequences support recent studies showing the presence of both B. mandrillaris (Lares-Jiménez et al, 2014) and N. fowlerii in soil (Moussa et al, 2015).…”
Section: Protist Parasitessupporting
confidence: 80%
“…Amoebic encephalitis can also be caused by Balamuthia mandrillaris and Naegleria fowleri (Excavata, Heterolobosea) (Visvesvara et al, 1993;Schuster and Visvesvara, 2004;Visvesvara et al, 2007;Siddiqui and Ahmed Khan, 2012). The finding of related SSU rRNA sequences support recent studies showing the presence of both B. mandrillaris (Lares-Jiménez et al, 2014) and N. fowlerii in soil (Moussa et al, 2015).…”
Section: Protist Parasitessupporting
confidence: 80%
“…In Guadeloupe (French West Indies), a fatal case of PAM occurred in 2008 after a child swam in a bath fed with geothermal waters [15]. In 2013, our group revealed that thermophilic FLA (and in particular, N. fowleri) were frequently detected in these baths [12]; the contamination of the water with N. fowleri occurs after emerging from the geothermal source, when the water runs over the soil [11]. We also observed that N. fowleri was often found at low concentrations, below 22 amoebae per liter [12].…”
Section: Introductionmentioning
confidence: 85%
“…Thermophilic FLA, and in particular Naegleria sp., have been frequently detected in Guadeloupe, in soil [11] and in natural thermal water [12]. French health authorities have endorsed a rule that forbids swimming or playing sports in natural water where the concentration of N. fowleri is above 100 amoebae/L [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N. fowleri showed 100% survival at pH ranging from 2.1 to 8.15 (220,221). Artificial heating of water by power plant discharges facilitates proliferation (222), however N. fowleri was not detected outside the reach of the thermal pollution (223), suggesting that warm discharge water should not be used for sports and entering the baths after rainfall, it is possible to reduce the concentration of amoebae in geothermal baths (232). N. fowleri has been isolated from hot springs in Yellowstone and Grand…”
Section: Ecologymentioning
confidence: 99%